Ethnic Peculiarities and Inter-ethnic Parallels in the Traditional Material Culture of the Hungarians of Ugocsa - Kész, Barnabás (Ethnographica et Folkloristica Carpathica, 2024)
The Hungarians living in the present-day Transcarpathian region have lived peacefully for centuries together with the majority Ruthenian/Ukrainian population, as well as with the Romanian, German, Roma and other ethnic groups, who live in a similar minority to the Hungarians. Ethnographers and tourists visiting the region are convinced that these nationalities have retained the characteristics of their culture to this day. At the same time, it is worth observing how this long historical coexistence is reflected in the way of life and mentality of these people. The parallels between Ruthenian and Hungarian language and folklore, folk customs are excellent examples of interethnic relations, but I have also encountered similar examples when researching the traditional material culture of the villages in Ugocsa. In the field of folk architecture, for example, the gate called tőkés kapu, as well as the abora, aszaló [the dryer] and the barn. Interethnic phenomena between Hungarians, Ruthenians and other nationalities of the region can also be observed in folk costumes (the guba, or the shoes called bochkor). Throughout history, in Transcarpathia, which belonged to different state formations, it was noticeable that culture was not strictly tied to peoples. Thanks to the tolerance shown towards each other, the nationalities of the region have preserved their ethnic and religious characteristics and identity, but we can also find many similarities in their cultures. When studying the interactions that mutually enrich each other’s culture and provide a colorful and attractive image to the region, it is often impossible to find out who borrowed from whom and when. During the ethnographic research of the local communities, the main point is to take into account the ethnic interaction of the nationalities living here, as the folk culture of the local Hungarians is determined by the aggregation of the cultures of different ethnicities.